المسؤولية القانونية لطبيب التخدير - علي محمد الكايد, زياد (revue mofakir; No 14 (2017): مجلـــة المفكــر, 2018)
This study addresses with the research and analysis of the legal responsibility of anesthetist during the performance of his work as a medical doctor, through an in-depth study and analysis of the legal opinions received in this responsibility, taking into account the position of jurisprudence and judicial responsibility, and historical development of the anesthesiologist's work and its relevance, which implies the importance of the study of the legal responsibility. This study has been divided into three chapters the first preview, we addressed the origins of Anesthesiology in General, through a concept of Anesthesiology and the historical background for this type of doctors, In the first chapter of the study we analyze the stages of the work of the anesthesiologist and what are the actions of the physician and the seriousness of its work on the patient, and the extent of its contribution to healing or death of the patient, the researcher have some important comments to be introduced for the benefit of this research, In the second chapter the researcher outline statement of liability incurred by the anesthesiologist due to work with judicial position where necessary, and in the end of the study findings and recommendations of the research.